2001
DOI: 10.1590/s0066-782x2001001100006
|View full text |Cite
|
Sign up to set email alerts
|

The Bambuí health and aging study (BHAS). Prevalence of intermittent claudication in the aged population of the community of Bambuí and its associated factors

Abstract: Disease prevalence was similar to that of other countries. The association between intermittent claudication and smoking strengthens the significance of tobacco in peripheral artery disease pathogenesis. The association of intermittent claudication and a higher number of hospital admissions suggests greater morbidity in the elderly affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
(17 reference statements)
1
7
0
2
Order By: Relevance
“…The transmission of this infection was interrupted in the study area decades before the beginning of the cohort study, but the prevalence of T. cruzi infection remained high among elderly residents through the operation of a cohort effect 17 . The prevalence of hypertension, diabetes mellitus, intermittent claudication and chronic knee or hand symptoms were comparable of those found in populations in rich countries 13,18,19 . Also, a high median level of total cholesterol was found, possibly reflecting dietary patterns of the Bambuí residents, with high lipid consumption, and low intake of fiber, vitamins, and minerals 20 .…”
Section: Characteristicssupporting
confidence: 65%
“…The transmission of this infection was interrupted in the study area decades before the beginning of the cohort study, but the prevalence of T. cruzi infection remained high among elderly residents through the operation of a cohort effect 17 . The prevalence of hypertension, diabetes mellitus, intermittent claudication and chronic knee or hand symptoms were comparable of those found in populations in rich countries 13,18,19 . Also, a high median level of total cholesterol was found, possibly reflecting dietary patterns of the Bambuí residents, with high lipid consumption, and low intake of fiber, vitamins, and minerals 20 .…”
Section: Characteristicssupporting
confidence: 65%
“…The Bambuí Project -to assess the prevalence of intermittent claudication in residents of Bambuí, in Minas Gerais State -used a Brazilian Portuguese version of the World Health Organization Questionnaire. However, no published data were found on questionnaire validation or on performance in Brazilian Portuguese 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of other risk factors such as smoking, diabetes mellitus, obesity and hypercholesterolemia, however, has also been recognized and their association with a higher LLOAD prevalence has been demonstrated [18][19][20] . In the present study, although patients were undergoing clinical treatment, it was observed that they maintained the habit of smoking, were overweight, and most were sedentary.…”
Section: Discussionmentioning
confidence: 99%